Accuracy of a drilling with a custom 3D printed guide or free‐hand technique in canine experimental sacroiliac luxations. Issue 1 (25th September 2021) - McCarthy, Daniel A.; Granger, L. Abbigail; Aulakh, Karanvir S.; Gines, J. Alberto
Abstract: Objective: To improve the accuracy of drilling during the repair of sacroiliac luxations (SILs) with a 3D‐printed patient‐specific drill guide (3D‐GDT) compared to free‐hand drilling technique (FHDT). Study design: Blinded, randomized, prospective ex vivo study. Sample population: Sixteen canine cadavers (20–25 kg). Methods: Dorsal, bilateral SILs were created. Pelvic CT was performed pre‐ and post‐drilling. The FHDT was drilled followed by 3D‐GDT. CT and 3D measurements of craniocaudal and dorsoventral angles were compared between FHDT and 3D‐GDT, as well as deviations of entry and exit points relative to optimal trajectory. Results: Mean craniocaudal and dorsoventral angles for both CT‐ and 3D‐measured 3D‐GDT (CT 4.2 ± 3.9° and 3.9 ± 3.2°, respectively; 3D 5.1 ± 5.1° and 2.8 ± 2.3°, respectively p = .0006) were lower compared to FHDT (CT 11.8 ± 4.0°, p < .0001 and 8.9 ± 6.1°, p = .01; 3D 12.4 ± 5.9°, p = .0006 and 5.3 ± 5.24°, p = .05). Entry dorsoventral and end craniocaudal, dorsoventral, and 3D linear deviations were reduced with 3D‐GDT. Sacral corridor disruption was present in 20% (3/15) for FHDT compared with 0% for 3D‐GDT. CT and 3D analyses were in strong agreement ( r = 0.77). Conclusion: Deviations of drill trajectories were minimized relative to optimal trajectories with 3D‐GDT compared to FHDT in the dorsoventral and craniocaudal planes. Clinical significance: The use of 3D‐GDT improves accuracy of sacral drilling compared with FHDT in canine cadavers. These results justify further evaluation in a clinical, prospective study.